Теоретико-методичні засади підвищення ефективності використання парку машин в регіональних транспортних системах та підприємствах на основі лізингових відносин - Аулін, В. В.; Ляшук, О. Л.; Гриньків, А. В.; Лисенко, С. В.; Гудь, В. З.; Тесля, В. О.; Aulin, V.; Liashuk, O.; Hrinkiv, А.; Lysenko, S.; Hud, V.; Teslia, V. (ЦНТУ, 2023)
В даній роботі розглядається проблема технічної та економічної ефективності придбання нових транспортних машин автотранспортними підприємствами регіону купівлею та за допомогою лізингових відносин з метою підвищення їх продуктивності і працездатності. Показано, що є необхідність у створенні теоретико-методичних засад лізингу транспортних машин, як одного із способів переоснащення системи машин в регіонах України та підвищення ефективності їх використання на основі лізингових відносин. Обґрунтовано, що при розробці засад доцільно базуватися на системі підвищення технічного стану машин відповідною стратегією їх технічного обслуговування і ремонту. Побудовано структурну схему системи транспортних машин регіону та автотранспортних підприємств, які мають модульну структуру рухомого складу. This work examines the problem of technical and economic efficiency of purchasing new transport vehicles by motor vehicle enterprises of the region by purchase and with the help of leasing relations in order to increase their productivity and efficiency. It is shown that there is a need to create the theoretical and methodological foundations of the leasing of transport vehicles, as one of the ways to re-equip the system of vehicles in the regions of Ukraine and increase the efficiency of their use on the basis of leasing relations. It is substantiated that when developing the foundations, it is expedient to base the system on improving the technical condition of machines with the appropriate strategy of their maintenance and repair. A structural diagram of the system of transport vehicles of the region and motor transport enterprises, which have a modular structure of rolling stock, was built. The main tasks in the development of issues of new leasing relations are outlined. When determining the number of leasing objects, the matrix of the system of technical effects of operations was used, according to the strategy of maintenance and repair of transport vehicles. When creating the theoretical and methodological foundations of the technical and economic efficiency of leasing, the costs for the implementation of maintenance and repair operations of transport vehicles were considered. It is noted that when leasing, it is important to assess the technical condition of transport vehicles by diagnosing them. The work defines the conditions under which it is expedient to develop leasing relations and when motor vehicle enterprises simply buy new vehicles. The sequence of the assessment of the corresponding costs is shown.
Theoretical and Methodological Principles of Increasing the Efficiency of the Use of a Fleet of Cars in Regional Transport Systems and Enterprises Based on Leasing Relations
Keywords: транспортна машина; теоретико-методичні засади; лізинг; технічне обслуговування і ремонт; транспортна система; автотранспортне підприємство; технічний стан; ефективність використання; transport vehicle; theoretical and methodological principles; leasing; maintenance and repair; transport system; motor vehicle enterprise; technical condition; efficiency of use